How childhood ADHD-like symptoms predict selection into entrepreneurship and implications on entrepreneurial performance - Rajah, Nasir; Bamiatzi, Vassiliki; Williams, Nick (Journal of Business Venturing, 2021)
This study advances research on mental health and entrepreneurship through the examination of Attention Deficit Hyperactivity Disorder (ADHD)-like symptoms, associated with hyperactivity/impulsivity and inattention. We examine the impact of these symptoms at age 10 on entrepreneurial performance as an adult. We find that while ADHD-like symptoms in childhood may have a positive impact on entrepreneurial selection, they negatively impact on survival and performance, with a variant effect by each symptom, predominantly among males. We find that high levels of inattention predict business failure and lower take-home income, while high levels of hyperactivity/impulsivity contribute to overall negative earnings' growth.